The Traumatic Experience in the Novel "The Perks of Being a Wallflower - Fuza Churil Khurotul Aini -; Khusnul Khotimah; Wahyu Indah Mala Rohmana (Channing : Journal of English Language Education and Literature, 2023)
This research investigates an experience of past trauma experienced by the main character in the novel The Perks of Being a Wallflower by Stephen Chbosky's. Charlie as the heroine, a 17-year-old boy, has just entered high school. . He is the youngest of a family of three, two boys, one girl He is a very quiet and shy child who makes him have no friends. Her strangeness made friends at her school bully her. The researchers' goal is to investigate the main symptoms of trauma and describe the trauma experiences in this novel. The researcher's method is descriptive qualitative. Supporting data sources include the novel The Perks of Being a Wallflower, online journals, theses and articles. The author refers to individual psychological theories that are used to analyze data. From the results of the author's analysis, that there are trauma experiences in the past that require him to find people to tell stories about the problems he is facing